When (im)perfective is perfect (and when it is not) - Olga Borik (Universitat Autònoma de Barcelona, 2018)
The goal of this paper is to discuss some meaning correspondences (and/or clashes) between the perfective/imperfective aspectual contrast in Russian and various interpretations of a perfect in English. While a detailed comparison between perfect and (im)perfective, even in only two specific languages, is a project that clearly extends beyond all imaginable page limits for a single paper, I hope to demonstrate here some tendencies which might facilitate further (and deeper) theoretical and empirical studies of these two highly debated grammatical categories. In particular, the paper will show that there is a clear split between perfective and imperfective aspect in the non-past tense with respect to expressing perfect meanings and there is also a split between different existential meanings of the perfect in the sense that some of them correspond to the perfective aspect and some of them are only rendered by the imperfective aspect in Russian. Given this empirical picture, one of the theoretical questions that emerges from this study is what kind of repercussions the observed generalizations might have for a (universal) grammatical theory of tense and aspect.